Afferent limb failure revisited – A retrospective, international, multicentre, cohort study of delayed rapid response team calls. (November 2020) - Tirkkonen, Joonas; Skrifvars, Markus B.; Tamminen, Tero; Parr, Michael J.A.; Hillman, Ken; Efendijev, Ilmar; Aneman, Anders
Abstract: Aim: The efficiency of rapid response teams (RRTs) is decreased by delays in activation of RRT (afferent limb failure, ALF). We categorized ALF by organ systems and investigated correlations with the vital signs subsequently observed by the RRT and associations with mortality. Methods: International, multicentre, retrospective cohort study including adult RRT patients without treatment limitations in 2017–2018 in one Australian and two Finnish tertiary hospitals. Results: A total of 5, 568 RRT patients' first RRT activations were included. In 927 patients (17%) ALF was present within 4 h before the RRT call, most commonly for respiratory criteria (419 patients, 7.5%). In 3516 patients (63%) overall, and in 756 (82%) of ALF patients, the RRT observed abnormal vital signs upon arrival. The organ-specific ALF corresponded to the RRT observations in 52% of cases for respiratory criteria, in 60% for haemodynamic criteria, in 55% for neurological criteria and in 52% of cases for multiple organ criteria. Only ALF for respiratory criteria was associated with increased hospital mortality (OR 1.71, 95% CI 1.29–2.27), whereas all, except haemodynamic, criteria at the time of RRT review were associated with increased hospital mortality. Conclusions: Vital signs were rarely normal upon RRT arrival in patients with ALF, while organ-specific ALF corresponded to subsequent RRT observations in just over half of cases. Our results suggest that systems mandating timely responses to abnormal respiratory criteria in particular may have potential to improve deteriorating patient outcomes.